Functional echocardiography identifies association between early ventricular dysfunction and outcome in pediatric sepsis - Reveco, Sonia; Barbagelata, Stella; Cruces, Pablo; Diaz, Franco; Yohanessen, Karla; Larraín, Marcos; Guerra, Mario; Bataszew, Alexander (Frontiers in Pediatrics, 2025)
ObjectiveThis feasibility study aimed to describe the relation between ventricular dysfunction and outcome in pediatric sepsis.MethodsThis prospective observational multicenter study was conducted in two Pediatric Intensive Care Units (PICU). We enrolled 51 patients aged younger than 15 year-old diagnosed with sepsis or septic shock. Functional echocardiography was performed by a pediatric intensivist within the first 24 h of admission and blind validated by a pediatric cardiologist. Ventricular dysfunction was defined by the presence of left or right systolic and/or diastolic dysfunction. The absence of these findings was considered normal ventricular function. Outcome was assessed by septic shock diagnosis rate, pediatric adaptation of Sequential Organ Failure Assessment (pSOFA), cardiovascular component of pSOFA, PICU-free and ventilator-free days.Results29 patients had sepsis, and 22 had septic shock. The main sites of infection were pulmonary (58.8%) and abdominal (17.6%). One out of four had ventricular dysfunction, and this group presented higher frequency of septic shock (69.2% vs. 34.2%, p = 0.028), higher frequency of total pSOFA ≥3 at 24 h (92% vs. 64%, p = 0.04), cardiovascular component of pSOFA (69.2% vs. 31.2%, p = 0.017), and fewer PICU-free days [18 [0–23] vs. 23 [18–25], p = 0.027], compared to normal ventricular function group. Additionally, there were more abnormal tissue doppler measurements, lower ś wave Z-Score [−0.6 [−1.3;0.4] vs. 0.5 [−0.2;1.1], p = 0.01] and lower é wave Z-Score [1.5 [−2;0,1] vs. −0.3 [−2;0.4], p = 0.03] in the ventricular dysfunction group.ConclusionVentricular dysfunction was associated with more sepsis severity at 24 hours, fewer PICU—free days. Tissue doppler parameters were related to ventricular dysfunction.